Eksplorasi Ilmu Sains dalam Tafsir Al-Qur’an: Pemahaman Konsep Penciptaan dalam Al-Qur'an dan Ilmu Biologi - Yusriyah; Akramun Nisa; Khaerunnisa (CV. Creative Tugu Pena, 2024)
This study aims to explore the relationship between the concept of creation in the Qur'an and modern biological theories, with a specific focus on integrating tafsir ilmi in understanding the creation of living beings. Through a literature review and thematic exegesis approach, this research examines Qur'anic verses related to the creation of humans and other living creatures, and compares them with contemporary biological theories. The findings reveal a harmony between the teachings of the Qur'an and scientific concepts, where both can complement each other in providing a deeper understanding of the creation process. This study also emphasizes the importance of integrating religion and science to reinforce the relevance of the Qur'an in the context of modern scientific advancements. These findings are expected to contribute to the development of a more integrative educational model and promote constructive dialogue between religion and science This study aims to explore the relationship between the concept of creation in the Qur'an and modern biological theories, with a specific focus on integrating tafsir ilmi in understanding the creation of living beings. Through a literature review and thematic exegesis approach, this research examines Qur'anic verses related to the creation of humans and other living creatures, and compares them with contemporary biological theories. The findings reveal a harmony between the teachings of the Qur'an and scientific concepts, where both can complement each other in providing a deeper understanding of the creation process. This study also emphasizes the importance of integrating religion and science to reinforce the relevance of the Qur'an in the context of modern scientific advancements. These findings are expected to contribute to the development of a more integrative educational model and promote constructive dialogue between religion and science